A Metabolism-Related Gene Prognostic Index Bridging Metabolic Signatures and Antitumor Immune Cycling in Head and Neck Squamous Cell Carcinoma - Du, Kunpeng; Zou, Jingwen; Wang, Baiyao; Liu, Chunshan; Khan, Muhammad; Xie, Tao; Huang, Xiaoting; Shen, Piao; Tian, Yunhong; Yuan, Yawei (Frontiers in Immunology, 2022)
Abstract Background: In the era of immunotherapy, predictive or prognostic biomarkers for Head and Neck Squamous Cell Carcinoma (HNSCC) are urgently needed. Metabolic reprogramming in the tumor microenvironment (TME) is a nonnegligible reason for the low therapeutic response to ICIs therapy. We aimed to construct a metabolism-related gene prognostic index (MRGPI) for HSNC bridging the metabolic characteristics and the anti-tumor immune cycling and identified the immunophenotype, genetic alternations, potential targeted inhibitors, and the benefit of immunotherapy in MRGPI-defined subgroups of HNSCC. Methods: Based on The Cancer Atlas (TCGA) HNSCC dataset (n = 502), metabolism-related hub genes were identified by the weighted gene co-expression network analysis (WGCNA). Seven genes were identified to construct MRGPI by using the Cox regression method and validated with an HNSCC dataset (n = 270) from the GEO database. Afterward, the prognostic value, metabolic activities, genetic alternations, GSEA, immunophenotype, cMAP, and the benefit of immunotherapy in MRGPI-defined subgroups were analyzed. Results: The MRGPI was constructed based on HPRT1, AGPAT4, AMY2B, ACADL, CKM, PLA2G2D, and ADA. Patients in the low-MRGPI group had better overall survival than those in the high-MRGPI group, consistent with the results in the GEO cohort (cut-off value = 1.01). Patients with a low MRGPI score display lower metabolic activities and an active antitumor immunity status and more benefit from immunotherapy. In contrast, a higher MRGPI score was correlated with higher metabolic activities, more TP53 mutation rate, lower antitumor immunity ability, an immunosuppressive TME, and less benefit from immunotherapy. Conclusion: MRGPI is a promising indicator to distinguish the prognosis, the metabolic, molecular, and immune phenotype, and the benefit from immunotherapy in HNSCC.